Multisite Case Study of Florida's Millennium High School Reform Model - Carol A. Mullen (Education Policy Analysis Archives, 2002)
This study should have immediate utility for the United States and beyond its borders. School-to-work approaches to comprehensive reform are increasingly expected of schools while legislative funding for this purpose gets pulled back. This multisite case study launches the first analysis of the New Millennium High School (NMHS) model in Florida. This improvement program relies upon exemplary leadership for preparing students for postsecondary education